Characterization of interactions of the Type IV secretion system core component VirB8 - Sivanesan, Durga (My University, 2010)
Type IV secretion systems (T4SS) are essential for the virulence of many gram-negative pathogens. The systems studied here comprise eleven VirB proteins in case of Agrobacterium tumefaciens and twelve in case of Brucella suis. The VirB proteins associate in the cell envelope and form a complex that mediates the translocation of virulence factors into host cells. In this report, VirB8, a core component of T4SS, is characterized with regards to its interaction with itself and with other VirB proteins.
VirB8 was found to exist in monomer-dimer equilibrium and the self-association was demonstrated by analytical ultracentrifugation, analytical gel filtration, surface plasmon resonance and bacterial two-hybrid assay. The above experiments demonstrated that residues M102, Y105 and E214 o fVirB8 from B. suis are involved in self-association and mutagenesis of these residues led to the impairment of T4SS function in B. suis. Furthermore, this information was utilized to unravel the contribution of VirB8 self-association towards T4SS assembly and function. To this end dimerization variants of VirB8 from Agrobacterium tumefaciens were created and the effects were assessed with purified proteins in vitro. Following this, the effects of VirB8 dimer site changes were assessed in vivo. Introduction of a cysteine residue at the predicted interface (V97C) supported DNA transfer but not T-pilus formation. Variants that reduced the self-association did not support T4SS functions and T-pilus formation. Moreover, VirB2- VirB5 co-fractionated with high molecular mass components from membranes of A. tumefaciens and VirB8 dimerization was shown to be necessary for VirB2 association with the high molecular mass components. Using purified VirB8 and VirB5 it was shown that VirB5 interacts with VirB8 via its globular domain and this interaction dissociates VirB8 dimers. Taking these results together, a mechanistic contribution of VirB8 dimerization to T4SS assembly was proposed.
Next, the interactions of VirB8 with other core components (VirB9 and VirBlO) were analyzed by using various in vitro and in vivo experiments. Purified soluble periplasmic domains of VirB8, VirB9 and VirB10 were used in enzyme-linked immunosorbent assays, circular dichroism, and surface plasmon resonance experiments. The pair-wise interactions and self-association of VirB8, VirB9 and VirB 10 were demonstrated with the in vitro experiments. In addition, a ternary complex formation between VirB8, VirB9, and VirBlO was identified. Using the bacterial two-hybrid system, the dynamics of the interactions between VirB8-VirB9-VirB 10 full-length proteins were analyzed demonstrating that VirB9 stimulates VirB8 self-association, but that it inhibits the VirB10-VirB10 as well as the VirB8-VirB10 interaction. Based on these results, a dynamic model for secretion system assembly is proposed where VirB8 plays a role as an assembly factor that is not closely associated with the functional core complex comprising VirB9 and VirB10.
The work reported in this thesis advances the understanding of VirB8 self-association and its contribution to T4SS assembly and function. Furthermore, the establishment of the bacterial two-hybrid system to detect VirB interactions has helped identify inhibitors for the VirB8 dimerization through collaboration with Dr. Athanasios Paschos. Moreover, techniques such as ELISA, analytical ultracentrifugation, circular dichroism and surface plasmon resonance will be utilized routinely to characterize other VirB-VirB interactions in future.
Keywords: Type IV secretion system; core component; VirB8; biology